2017
DOI: 10.1002/pd.5039
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome aneuploidy detection by noninvasive prenatal testing: helpful or hazardous?

Abstract: Sex chromosome aneuploidy was frequently suspected on NIPT. False positive rate for monosomy X was surprisingly high (91%). Prediction of other SCA was more accurate. Diagnostic fetal chromosome analysis should be offered after abnormal NIPT or in the presence of cystic hygromas despite normal NIPT. NIPT limitations should be explained in pretest counseling. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 26 publications
8
65
1
Order By: Relevance
“…The majority of the published data regarding positive and negative predictive values comes from commercial labs in addition to a few retrospective studies from clinical practices . These prior case series have shown that inclusion of SCAs on NIPT platforms doubles the overall positive screening rate and increases the false positive rate . The true positive rate for monosomy X especially is much lower as compared to autosomal trisomies most likely because of maternal and placental mosaicism …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the published data regarding positive and negative predictive values comes from commercial labs in addition to a few retrospective studies from clinical practices . These prior case series have shown that inclusion of SCAs on NIPT platforms doubles the overall positive screening rate and increases the false positive rate . The true positive rate for monosomy X especially is much lower as compared to autosomal trisomies most likely because of maternal and placental mosaicism …”
Section: Introductionmentioning
confidence: 99%
“…These prior case series have shown that inclusion of SCAs on NIPT platforms doubles the overall positive screening rate and increases the false positive rate . The true positive rate for monosomy X especially is much lower as compared to autosomal trisomies most likely because of maternal and placental mosaicism …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…What about the detection of SCAs? Several studies report sensitivities of between 50 and 100% for 45,X and 47,XXX, 47,XXY, and 47,XYY, but as negative cases are not karyotyped and follow‐up is generally poor, the true sensitivity is not known . These and other studies report false‐positive rates of 0.12 to 1.1% and PPVs of between 9 and 40% for 45,X, the most common sex chromosome anomaly, and 7 to 70% for the others.…”
Section: Against (Lyn Chitty)mentioning
confidence: 99%